Pengaruh keluarga dan efikasi diri dalam membuat keputusan karier: Mediasi identitas vokasi - Dwiyanthi, Putri Novie; Rostiana, Anisa; Riasnugrahani, Missiliana (Konsorsium Psikologi Ilmiah Nusantara, 2025)
This study aims to examine the influence of family on the career decision-making self-efficacy of final-year students, with a particular focus on the mediating role of vocational identity. The study involved 197 students from various public and private universities in Bandung, selected through a snowball sampling technique. Participants completed the Career Decision-Making Self-Efficacy Scale-Short Form, Family Influence Scale, and the Vocational Identity Measure, which all demonstrated high validity and reliability. Using Hayes’ PROCESS model 4 analysis, the results showed that vocational identity serves as a significant partial mediator in the relationship between family influence and career decision-making self-efficacy, with the indirect effect exceeding the direct effect. These findings suggest that family influence enhances students’ career decision-making self-efficacy by fostering their vocational identity. When students develop a strong vocational identity, supported by their parents, they become more confident in making career-related decisions.